Influence of silvopastoral systems on the feeding behavior of Holstein dairy cows - Benavides Rosales, Hernán Rigoberto; López Cevallos, Evelyn Nathaly; López Cevallos, Franklin Ernesto; Vivas Peñafiel, Gina Valeria (SATHIRI, 2020)
The role that trees have in silvopastoral systems shows multiple benefits in livestock production, so that was proposed to evaluate the feeding behavior of dairy cows in agro-ecosystems with Aliso (Alnus acuminata Kunth) plus grass, Acacia (Acacia melanoxylon R. Brown) plus grass and only pasture, in a period of six months using seven Holstein cows per Jersey in each agro-ecosystem, and evaluating the activities: time of consumption of grass, rumination and rest. In the same way, the differences in eating behavior were determined over time and the different agro-ecosystems, the data collected was analyzed using a completely randomized design, the Kruskal Wallis statistical test and the Median of Mood it was demonstrated that animals dedícate more time to consuming pasture (50.87 %) in the July-August two-month period, followed by rest (29.30 %) in the March-April two-month period and rumination (28.40 %) in the May-June two-month period, being statistically significant (p
Keywords: Eating behavior; consumption; rumination; rest